The Dixiecrat revolt and the end of the solid South, 1932-1968 - Frederickson, Kari A. (The University of North Carolina Press, 2001)
In 1948 a group of conservative white southerners formed the States' Rights Democratic Party, soon nicknamed the "Dixiecrats". This volume situates the Dixiecrat movement within the tumultuous social and economic milieu of the 1930s and 1940s South.